Speed endurance training to improve performance - Bangsbo, J.; Kissow, J.; Hostrup, M. (Scandinavian Journal of Medicine & Science in Sports, 2025)
In many sports, the physical dimension plays a crucial role in determining athletic performance. This review provides insights into the effectiveness of speed endurance training (SET), that is, exercise training performed at intensities higher than that eliciting maximum oxygen uptake (VO2-max), on performance across different sports and event durations, that is, lasting 20-60 s, 1-10 min, and 10-60 min, as well as repeated intense exercise, as found in sports like football and basketball. Only studies with trained subjects and athletes are reviewed. For each event, the description is divided into the effect of SET, either alone or in combination with aerobic training or power/resistance training. We highlight that SET enhances performance across all event durations, even when training volume is markedly reduced. The performance enhancements arise despite no changes in VO2-max and are typically associated with improved exercise economy and a greater capacity to handle muscle ionic shifts and counter exercise-induced reductions in pH. Thus, athletes can benefit from periods with SET—either performed alone or in combination with other training modalities.